Budaya Organisasi Pondok Pesantren Darussalam Blokagung Banyuwangi - Moh. Imam Khaudli; Ikhsan Mubarok (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The objectives set from this research are (1) to find out the Organizational Culture that develops in the Darussalam Boarding School in Blokagung (2) to find out the main role of the Kiai as the main maker of the Culture of the Darussalam Boarding School in Blokagung Tgalsari Banyuwangi. This study uses descriptive qualitative research methods. In this study the researcher himself became (human instrument) with supporters of the interview guide grid, data collection is more emphasized on observation, interviews and documentation. The validity of the data in this study uses data triangulation. The results of his research on Organizational Culture at the Message Board of Darussalam Blokagung Tegalsari Banyuwangi were formed by several elements (1) the environment of the Darussalam Block Corn boarding school at its inception. (2) Values and the norms that have been taught by KH. Mukhtar Syafa'at Abdul Ghofur as the founder of a boarding school that has been sustainable until now. (3) Darussalam Blokagung pesantren rituals and traditions are one of the learning system activities and also other activities such as the typical 10 muharam activities, as well as other activities that have become an identity and shaped the organizational culture. (4) A role model or hero, the researcher considers this element to be the most important of the other elements because the characteristics and center of the creator in an organization are the leaders of the kiai (5) cultural network, this element is an informal communication between elements in Darussalam boarding schools Blokagung and develop by itself and become the identity of the cottage. And in Darussalam boarding school Blockagung kiai as the main leader and also plays a full role as (1) organizational activator (2) creator of Organizational Culture (3) cultural preserver and (4) as an agent of change.